2020
DOI: 10.7554/elife.54385
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy in the adult Drosophila brain

Abstract: Long-lived cells such as terminally differentiated postmitotic neurons and glia must cope with the accumulation of damage over the course of an animal’s lifespan. How long-lived cells deal with ageing-related damage is poorly understood. Here we show that polyploid cells accumulate in the adult fly brain and that polyploidy protects against DNA damage-induced cell death. Multiple types of neurons and glia that are diploid at eclosion, become polyploid in the adult Drosophila brain. The optic lobes exhibit the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 92 publications
5
44
1
Order By: Relevance
“…Our recent work has shown that neurons and glia become polyploid in the fly brain, specifically in the adult ( Nandakumar et al, 2020 ). Our study found that the optic lobes show higher levels of polyploidy than the central brain and the ventral nerve cord.…”
Section: Are All Terminally Differentiated Neurons Permanently Diploid and In G0?mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent work has shown that neurons and glia become polyploid in the fly brain, specifically in the adult ( Nandakumar et al, 2020 ). Our study found that the optic lobes show higher levels of polyploidy than the central brain and the ventral nerve cord.…”
Section: Are All Terminally Differentiated Neurons Permanently Diploid and In G0?mentioning
confidence: 99%
“…In Drosophila , the enterocytes of the intestinal epithelium, the follicle cells of the ovary and the main cells of the accessory gland can cope with induced cell death by engaging a compensatory cellular hypertrophy or endocycle program to maintain tissue size and homeostasis ( Tamori and Deng, 2013 ; Edgar et al, 2014 ; Shu et al, 2018 ; Øvrebø and Edgar, 2018 ; Box et al, 2019 ). In the fly optic lobe, where increase in polyploidy is accompanied by a steady loss of diploid cells, polyploidization may serve a compensatory role by enabling neurons to form more synaptic connections to compensate for cell loss to maintain visual acuity ( Nandakumar et al, 2020 ).…”
Section: Are All Terminally Differentiated Neurons Permanently Diploid and In G0?mentioning
confidence: 99%
“…For example, we describe variation amongst three WT Drosophila strains in the level of accumulating eccDNAs containing TE sequences (Fig. 5), while others have shown increased in polyploidy in adult Drosophila brains [110] as well as somatic genome instability in regions of the Drosophila genome [111] that might contribute to changes at the level of TE consensus sequence coverages (Fig. S3B).…”
Section: Discussionmentioning
confidence: 94%
“…Together, these findings confirmed that there are cells in S phase in the adult brain (Figure 2b). However, S-phase markers can also reveal polyploid cells, present in the adult brain [38].…”
Section: There Are Proliferating Cells In the Adult Drosophila Brainmentioning
confidence: 99%
“…[2,3,27] Polyploidy in the adult brain. [38] Inference of mitosis from MARCM clones. Clones induced in the adult brain generated both glial and neuronal progeny cells.…”
Section: Cell Proliferationmentioning
confidence: 99%